PONDOK PESANTREN EKOLOGI AT THORIQ: Dari Sustainability Alam Menuju Kemandirian Ekonomi - Maula, Inayatul (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
This research will examine two important issues, first, issues related to ecology with all the scope of the problem. Second, issues related to economic independence. These two important issues are underwritten by Pondok Pesantren as a basis and value in solving ecological problems and economic independence. Theoretical studies of Islamic boarding schools' values originating from the treasures of